The Standard periodical directory. (New York Oxbridge Communications, 1995)
Annual, 1989- Biennial Irregular, 1977-1987 1965-1973
This directory may be used to identify specialized trade journals as possible sources of business information or advertising.
Keywords: American periodicals -- Directories; Canadian periodicals -- Directories; Periodicals -- Canada -- bibliography; Periodicals -- United States -- bibliography